Penanaman Tanaman Obat Keluarga (TOGA) Sebagai Salah Satu Usaha Pemberdayaan Siswa Dalam Menumbuhkan Kepedulian Kesehatan Keluarga - Lina Agustina; Dwi Wahyu Permatasari; Ellen Fatimah Miftahul Jannah; Mirza Julia Nurcahyani (Universitas Sebelas Maret, 2023)
Utilization of TOGA (Family Medicinal Plants) is one way that can anticipate and overcome family health problems. Family medicinal plants (TOGA) are used to anticipate or treat independently using existing medicinal plants. Family medicinal plants have many benefits so we carry out activities regarding the introduction and planting of family medicinal plants. The aim of this activity is to increase the knowledge of students at SMP Negeri 4 Satu Atap, Ngaringan, Grobogan in cultivation and using family medicinal plants as an effort to promote awareness of family health. The method used is to socialize the importance and benefits of TOGA to the school community, especially to students in class VII and class VIII, followed by cultivation TOGA in schools. The results of this activity show that students' knowledge has increased regarding the use of TOGA and their concern for family health has grown.